On the centrality of redemption: Linking the state and credit theories of money through a financial approach to money - Éric Tymoigne (Levy Economics Institute of Bard College, 2017)
The paper presents a financial approach to monetary analysis that links the credit and state theories of money. A premise of the functional approach to money is that "money is what money does." In this approach, monetary and mercantile mechanics are conflated, which leads to the conclusion that unconvertible monetary instruments are worthless. The financial approach to money strictly separates the two mechanics and argues that major monetary disruptions occurred when the two were conflated. Monetary instruments have always been promissory notes. As such, their financial characteristics are central to their value and liquidity. One of the main financial requirements of any monetary instrument is that it be redeemable at any time. As long as this is the case, the fair value of an unconvertible monetary instrument is its face value. While the functional approach does not recognize the centrality of redemption, the paper shows that redemption plays a critical role in the state and credit views of money. Payments due to issuer and/or convertibility on demand are central to the possibility of par circulation. The paper shows that this has major implications for monetary analysis, both in terms of understanding monetary history and in terms of performing monetary analysis.
Keywords: E31; E42; G12; 330; Credit Theory of Money; State Theory of Money; Net Present Value; Monetary Systems